1995
DOI: 10.1111/j.1365-2141.1995.tb05603.x
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 8 in acute promyelocytic leukaemia: an interphase study by fluorescence in situ hybridization

Abstract: Acute promyelocytic leukaemia (APL) is characterized by t(15;17)(q24;q21). Trisomy 8 is the commonest accompanying karyotypic aberration. We investigated 14 APL patients for trisomy 8 using fluorescence in situ hybridization (FISH). Conventional cytogenetic analysis showed trisomy 8 in two of nine successfully karyotyped cases. With FISH, a possible third case showing a subclone (1-2.5%) with trisomy 8 was found. The trisomy 8 clone size defined by karyotyping and FISH was concordant in one case and discordant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…All consecutive cases of APL diagnosed between 1995 and 2002 were studied. The diagnosis was confirmed with cytogenetic analysis, fluorescence in situ hybridization (Ma et al , 2000) and reverse transcription polymerase chain reaction (RT‐PCR) as reported (Kwong et al , 1995). The short and long PML/RAR α fusion products ( PML break at BCR3 and BCR1 respectively) were determined from the size of RT‐PCR product.…”
Section: Patientsmentioning
confidence: 70%
“…All consecutive cases of APL diagnosed between 1995 and 2002 were studied. The diagnosis was confirmed with cytogenetic analysis, fluorescence in situ hybridization (Ma et al , 2000) and reverse transcription polymerase chain reaction (RT‐PCR) as reported (Kwong et al , 1995). The short and long PML/RAR α fusion products ( PML break at BCR3 and BCR1 respectively) were determined from the size of RT‐PCR product.…”
Section: Patientsmentioning
confidence: 70%
“…The diagnosis of APL was based on the World Health Organization criteria, and confirmed by the presence of t(15;17) on karyotyping or fluorescence in‐situ hybridization (FISH), and PML ‐ RARA molecularly. Molecular monitoring for PML ‐ RARA was performed on the peripheral blood by reverse transcription polymerase chain reaction with a sensitivity of 10 −5 as previously reported 12. For newly diagnosed APL, the modified MRC AML12 protocol for AML was used 13.…”
Section: Case Reportsmentioning
confidence: 99%
“…On reaching a third complete remission (CR3), she was consolidated with idarubicin (Kwong et al , 2001). However, PML/RARA remained positive using a standard reverse transcription polymerase chain reaction (Kwong et al , 1995), with a sensitivity of 1 × 10 −4 . A third haematological relapse occurred 15 months later.…”
Section: Patients and Resultsmentioning
confidence: 99%